Projection of the number of students and their acceptance at various educational levels until 2025 - Gayuh Nugroho Dwi Putranto; Juliadi Nugroho; Muhammad Zid; Cahyadi Setiawan (Graduate School, Universitas Negeri Yogyakarta, 2020)
The 1945 Constitution states that education is a right for every citizen. Education is a conscious and planned effort to realize the atmosphere of learning and the learning process so that students can develop their potential. Education in Indonesia aims to educate the nation's life. Indonesia's education system in its development continues to make changes. The zoning policy in education is one form of positive response from the government to equalize education in each region. The zoning policy requires each student to go to school the closest distance from their residence. Schools provide about 90% of the student capacity measured by distance. The zoning policy in its development still leaves various problems. A common problem is the unavailability of educational facilities in a sub-district area so that some students have the potential to not go to school. Bekasi City is a metropolitan city that serves as a buffer for the capital city. In its development, Bekasi City has the potential to experience problems of inequality in the number of students and absorption in schools. This study aims to project the number of students and their absorption at various levels of education in Bekasi until 2025.